The 50 Greatest Players in St. Louis Cardinals History - Cohen, Robert W. (Rowman & Littlefield Publishers, 2013)
The St. Louis Cardinals are perhaps the most popular and successful franchise in National League history, having won more world championships than any other club in the league. Baseball greats such as Stan Musial, Rogers Hornsby, and Albert Pujols have all worn the Cardinals uniform. But which Cardinals are the finest in franchise history? Examining every player who has donned the Redbird uniform since 1892, Robert W. Cohen ranks the best of the best in The 50 Greatest Players in St. Louis Cardinals History. This book carefully studies the careers of the players who made the greatest impact while playing for the St. Louis Cardinals. The ranking was determined based on such factors as the extent to which each player added to the Cardinals legacy, the degree to which he impacted the fortunes of his team, and the level of dominance he attained while wearing the Redbird uniform. Features of The 50 Greatest Players in St. Louis Cardinals History include: Each player’s notable achievements Recaps of the player’s most memorable performances Summaries of each player’s best season Quotes from opposing players and former teammates Including players such as Bob Gibson, Ozzie Smith, Lou Brock, and Mark McGwire, this book is sure to fuel debate among Cardinals fans. A fascinating collection of bios, stats, recaps, quotes, and more, The 50 Greatest Players in St. Louis Cardinals History is a must-read not only for die-hard Cardinals fans, but for all fans of baseball.